Efeitos dos pisos salariais estaduais sobre o mercado de trabalho: Uma nova abordagem empírica - Carlos Henrique Corseuil; Miguel Foguel; Marcos Hecksher (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This paper aims to evaluate the introduction of Brazilian regional and occupational wage floors on labor market performance. We focus on two out of five states that implemented such policy intervention, which are Paraná and S\~ao Paulo. In each region, we have analyzed data for three distinct occupational categories. Our results point that one occupational group in each region seems to be affected by the introduction of a wage floor. In both cases, the wage floor tends to lower the share of employees with wages below the floor, without producing side effect neither on employment nor on informality. In particular, employment appears to have reacted positively. It was found no significant effect of the legislation in the other occupational groups. We innovate on methodological grounds by using the synthetic control method due to Abadie, Diamond and Hainmueller (2010).
Keywords: J21; J31; J38; 330; minimum wages; treatment effect